Interfacial tension of PBT/SAN blends by the drop retraction method - Ito, Edson Noriyuki (2008)
The aim of this work was to evaluate the interfacial tension from the poly(butylene terephtalate) and poly(styrene-co-acrylonitrile) (PBT/SAN) interface region using the drop retraction method. SAN filaments were sandwiched between two PBT films; the whole system was heated up to 240 °C, in a hot stage coupled to an optical microscope. The rheological parameters of the PBT/SAN system were obtained by parallel plates rheometry. An increase of the interfacial tension with the PBT molecular weight was observed with values between 0.57 and 1.06 mN/m, depending on the molecular weight. Theoretical values were calculated using the geometric-mean and harmonic-mean equations and were found to be similar to the experimental results. Viscosity measurements showed that the higher the SAN/PBT viscosity ratio, the lower the interfacial tension of these blends